2022
DOI: 10.3390/cells11213469
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Are Key Host Immune Effector Cells Affecting Survival in Autologous Peripheral Blood Hematopoietic Stem Cell Transplantation

Abstract: The infusion of autograft immune effector cells directly impacts the clinical outcomes of patients treated with autologous peripheral blood hematopoietic stem cell transplantation, suggesting the possibility of an autologous graft-versus tumor cells. Furthermore, the early recovery of immune effector cells also affects survival post-autologous peripheral blood hematopoietic stem cell transplantation. Natural killer cells are among the immune effector cells reported to be collected, infused, and recovered early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…NK cells phenotype changes during the immune system reconstitution after autoHSCT 12,24,25,27 . In this work we have studied the NK cell reconstitution in a cohort of 13 pediatric patients with cancer undergoing autoHSCT using blood samples taken at different time points: before autoHSCT (S1), after reaching leucocyte recovery (>1000 leukocytes/µl, usually around day 12 after autoHSCT, S2) and 30 days (S3), 100 days (S4) and 180 days (S5) after autoHSCT.…”
Section: Nk Cell Counts Subset Frequencies and Maturation Status Afte...mentioning
confidence: 99%
See 2 more Smart Citations
“…NK cells phenotype changes during the immune system reconstitution after autoHSCT 12,24,25,27 . In this work we have studied the NK cell reconstitution in a cohort of 13 pediatric patients with cancer undergoing autoHSCT using blood samples taken at different time points: before autoHSCT (S1), after reaching leucocyte recovery (>1000 leukocytes/µl, usually around day 12 after autoHSCT, S2) and 30 days (S3), 100 days (S4) and 180 days (S5) after autoHSCT.…”
Section: Nk Cell Counts Subset Frequencies and Maturation Status Afte...mentioning
confidence: 99%
“…In addition, it has been described that the number of NK cells and the frequency of several subsets are associated with survival 12,27 . For example, it has been shown that MM patients with lower frequencies of the mature highly differentiated NKG2A-CD57+ NK cell subset after autoHSCT had a better outcome 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary end points of this study were the impact of Day 100 NKC/CD14 + HLA-DR DIM ratio on overall survival (OS) and progression-free survival (PFS). The secondary end points of the study included: (1) to assess if Day 100 NKC/CD14 + HLA-DR DIM ratio further discriminate survival in patients with a day 100 negative Positron Emission Tomography (PET) scan, and (2) to assess if the combination of the autograft and Day 100 NKC/CD14 + HLA-DR DIM ratios predicts OS and PFS.…”
Section: End Pointsmentioning
confidence: 99%
“…Natural killer cells 1 and CD14 + HLA‐DR DIM cells 2,3 have been reported to be immune effector cells affecting survival in lymphoma patients treated with autologous peripheral blood hematopoietic stem cell transplantation (APBHSCT). Our group previously published that the infusion of autograft Natural Killer Cells (NKC)/CD14 + HLA‐DR DIM ratio ≥.29, as a surrogate marker of host immunity (NKC) and tumor microenvironment (CD14 + HLA‐DR DIM ), was a predictor of clinical outcomes of lymphoma patients post APBHSCT 4 .…”
Section: Introductionmentioning
confidence: 99%